2021
DOI: 10.1002/asia.202100526
|View full text |Cite
|
Sign up to set email alerts
|

A ZIF‐8 Host for Dendrite‐Free Zinc Anodes and N,O Dual‐doped Carbon Cathodes for High‐Performance Zinc‐Ion Hybrid Capacitors

Abstract: Zn is a promising anode for aqueous energy storage owing to it intrinsic superior properties such as large capacity, abundant reserves, low potential and safety. But, the growth of dendrites during charge and discharge leads to a decrease in reversibility. In addition, further development of zinc‐ion hybrid capacitors (ZICs) is seriously challenging because of the lack of an exceptional cathode. Herein, we use ZIF‐8 annealed at 500 °C (annealed ZIF‐8) as a host material for stable and dendrite‐free Zn anodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Subsequently, Zn@ZIF-8-500 anode is coupled with activated carbon cathode to form ZHSCs and delivered an energy density of 140.8 Wh kg −1 as well as splendid longevity up to 20,000 cycles. Similarly, Shen et al employed annealed ZIF-8 as the substrate of dendrite-free Zn anode and Zapien et al deposited the Zn onto the flexible carbon cloth (CC) [98,99]. The combination of electrodeposited Zn and carbon materials enables the composite Zn anode outstanding properties for highperformance ZHSCs.…”
Section: Electrodeposited Nanostructure Zn Anodementioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, Zn@ZIF-8-500 anode is coupled with activated carbon cathode to form ZHSCs and delivered an energy density of 140.8 Wh kg −1 as well as splendid longevity up to 20,000 cycles. Similarly, Shen et al employed annealed ZIF-8 as the substrate of dendrite-free Zn anode and Zapien et al deposited the Zn onto the flexible carbon cloth (CC) [98,99]. The combination of electrodeposited Zn and carbon materials enables the composite Zn anode outstanding properties for highperformance ZHSCs.…”
Section: Electrodeposited Nanostructure Zn Anodementioning
confidence: 99%
“…Lu et al reported molten salt-assisted synthesis of pitch-derived PCs cathodes for Zn//Cap ZHSCs while Guan et al proposed bamboo-derived PCs cathodes with superb stability when employed in ZHSCs (96% capacity retention after 90,000 cycles) [114,115]. Moreover, Xu et al and Shen et al reported a MOF route for fabricating PCs electrode materials, the ZIF-8-derived PCs presented an splendid performance of 225 mAh g −1 at 0.1 A g −1 and remained 135.5 mAh g −1 at 1 A g −1 [98,116]. As depicted in Fig.…”
Section: Hssa Carbon Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of electrodeposited zinc and substrates or hosts is also crucial for high-performance zinc anodes. [83,84,109] Leng et al [83] prepared a modified CC with pregrown ZIF-8 (CC/ZIF-8) as the substrate for zinc formation. Dendrite-free ZHSCs were effectively built using CC/ZIF-8, because the ZIF-8 lowers the nucleation barrier of zinc, allowing for quick and uniform Zn formation.…”
Section: Zinc Foil Improvementmentioning
confidence: 99%